2019
DOI: 10.1155/2019/2098492
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hull Girder Ultimate Strength and Residual Strength Based on IACS CSR‐H

Abstract: In order to express the safety level of hull structures, IACS Common Structure Rules of Bulk Carriers and Oil Tankers (CSR-H) makes new requirements of hull girder ultimate strength. Compared with original CSR (i.e., CSR-OT and CSR-BC), partial safety factors of hull girder ultimate strength in CSR-H have been partly modified, and new requirements of residual strength have been added in the rules for hull safety after grounded/collided damage. This paper compares the rule requirements of ultimate strength in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Experimental and numerical investigations on the ultimate strength of stiffened plates subjected to combined biaxial compression and lateral loads showed that lateral pressure enhanced the loadcarrying capacity when the lateral force restrained deformation, as investigated by Ma et al [6]. Further, the ultimate and residual strength of a hull girder based on IACS CSR-H,CSR-OT, and CSR-BC were compared in detail by Shi et al [7]. In a series of recent studies, more advanced analyses of stiffened ship structures subjected to impact phenomena were performed to identify structural damage caused by striking and stranding, including ship-ship collision accidents [8][9][10][11][12], ship grounding [13][14][15][16][17], and other forms of ship hull damage [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and numerical investigations on the ultimate strength of stiffened plates subjected to combined biaxial compression and lateral loads showed that lateral pressure enhanced the loadcarrying capacity when the lateral force restrained deformation, as investigated by Ma et al [6]. Further, the ultimate and residual strength of a hull girder based on IACS CSR-H,CSR-OT, and CSR-BC were compared in detail by Shi et al [7]. In a series of recent studies, more advanced analyses of stiffened ship structures subjected to impact phenomena were performed to identify structural damage caused by striking and stranding, including ship-ship collision accidents [8][9][10][11][12], ship grounding [13][14][15][16][17], and other forms of ship hull damage [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%